Virtual E-participation in Saving the Environment in the Digital Age Through Change.org - Rosmita Rosmita; Eko Priyo Purnomo; Nuryanti Mustari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The purpose of this research is to see how the role of the Change.org website and how the Change.org account interacts with Twitter social media accounts through mentions that are used to increase public awareness of the environment. This study uses qualitative research, which uses Q-DAS (Qualitative Data Analysis Software) to analyze the data using Nvivo 12 Plus and Vosviewer software. The results of this study indicate that Change.org, in voicing environmental cleanliness, uses social media as a media campaign. The social media used by Change.org itself is Twitter. The change.org Twitter account is one of the largest environmental petitions; the form petition carried out by Change.org is by calling on @Cocacola @McDonalds and BurgerKing, which contains various petitions to find solutions for plastic bottles, which many say are choking the environment. The ability of online petitions to facilitate requests for change in public policies and connect the public with policymakers shows that online petitions can increase individual and group political participation. The existence of a petition on the @Change.org Account can gradually save the environment.